A profitability study on the Malaysian futures markets using a new adjustable technical analysis indicator, adjustable bands Z-test-statistics' (ABZ') - Mohamed, I.; Azizan, N.A.; Chan, J.P.M. (Academic Journals, 2011)
Financial markets all over the world generally exist in 2 conditions: trending and ranging. One of the most frustrating issues confronting market technicians daily is the critical definition when market is ranging and when the market is trending. Applying a trending algorithm to a ranging market will result in whipsaws that yield losses. To avoid some of these false entry signals, this research proposed to vary the moving average and standard deviation parameters to avoid some of these false entry whipsaws and yet capture a new trend early. Adaptive algorithm like the Adjustable Bands Z-Test-Statistics' (ABZ'), seeked to provide a solution to this issue. For the year 2008, ABZ' showed an abnormal return of 316 index points for Malaysian Kuala Lumpur Composite Index Futures (FKLI) compared with a negative return of -562 index points for the passive buy-and-hold strategy and 690 for Malaysian Crude Palm Oil Futures (FCPO) compared with a negative return of -1387. Results from this research interest investors world wide who are trying to overcome this baffling issue of ranging versus trending markets.